Sharing Information: Report on the LIBER Library Security Network (LSN) Since 2002 - Nielsen, Erland Kolding (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
On 2 July 2002, the Executive Board of LIBER, in line with the Copenhagen Principles of 14 May 2002, endorsed the establishment of a Library Security Network to facilitate the exchange of confidential security information among European national, university and other important research libraries with valuable collections. The Network came into being at the end of 2002. It has now been running for more than five years. The objective was, and is, to create a safe information and communication network, based on e-mail, for European library directors and security managers. This paper aims to review the experience: Has the system worked? Has it helped in terms of preventing crime, in solving crimes, in raising security awareness among the member institutions? Furthermore, the aim is to contribute to a revision in the broader perspective of a European context: Is it enough? Should it work otherwise? Are there other channels of information? Should the Network be expanded?